Effectiveness and Perceptions of Low-Achieving Students onthe Use of YouTube in Learning Geography - Ahmad Sulaiman, Zuraidah; Abdul Hanid, Mohd Fadzil; Nordin, Nurul Syaheeda (Journal of Research, Innovation, and Strategies for Education (RISE), 2024)
The use of educational technology has been widely used by teachers in the era of the 21st century. This study aims to see the perception of weak students on towards the use of Youtube as well as the effectiveness of learning Geography in rural school in learning the topic of physical Geography. This study was conducted in several secondary schools that rural schools in the Muar Johor district. The selection of rural schools in the district used simple random sampling. The design of this study uses a quasi-experimental method that consists of two groups and uses a quantitative approach in the process of data collection and data analysis. The study sample is form 3 students consisting of 60 students who are divided into two groups, namely the control group and the treatment group. The research instrument used is a set of achievement questions to measure the level of achievement and a questionnaire given to the treatment group with the aim of studying the perception of weak students towards the use of YouTube and its effectiveness. The use technology in various methods can stimulate the learning process of students and can have an effective impact. However, in learning Geography, there are many facts that need to be remembered and understood, so due to this problem, students are easily bored and lose interest in knowing them, resulting in an unsatisfactory level of achievement. The findings of the study show that for weak students in rural area, the learning strategy of using this application, it gives a positive effect. The conclusion, of this study will be able to help educators find a variety of learning strategies for weak students in rural areas to facilitate the process of remembering and understanding facts and concepts in learning Geography on the topic of Physical Geography.
Keywords: Geography; Physical Geography; Youtube; Educational Technology; Video